2020
DOI: 10.3389/fmicb.2020.01872
|View full text |Cite
|
Sign up to set email alerts
|

Designing Safer CRISPR/Cas9 Therapeutics for HIV: Defining Factors That Regulate and Technologies Used to Detect Off-Target Editing

Abstract: Human immunodeficiency virus type-1 (HIV-1) infection has resulted in the death of upward of 39 million people since being discovered in the early 1980s. A cure strategy for HIV-1 has eluded scientists, but gene editing technologies such as clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) offer a new approach to developing a cure for HIV infection. While the CRISPR/Cas9 system has been used successfully in a number of different types of studies, there remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…CRISPR technology is becoming the leading gene editing tool, with increasingly expanding fields of application 11, 41 . These include HIV therapy, where CRISPR might allow excision of the integrated HIV genome, which can be excised from cellular DNA by taking advantage of CRISPR/Cas9 site-specific cleavage 42, 43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CRISPR technology is becoming the leading gene editing tool, with increasingly expanding fields of application 11, 41 . These include HIV therapy, where CRISPR might allow excision of the integrated HIV genome, which can be excised from cellular DNA by taking advantage of CRISPR/Cas9 site-specific cleavage 42, 43 .…”
Section: Discussionmentioning
confidence: 99%
“…This approach has proven to be effective and potent in vitro , whereas a number of limitations may be relevant when it is transposed in vivo . CRISPR/Cas9 may exhibit possible off-target activity and defiant gene rearrangement following DNA repair 41, 44 ; moreover, diversity and mutations of HIV genome may constrain target selection 4547 . Lastly, site of integration and transcriptional activity of the provirus may impact on susceptibility to CRISPR cleavage 4750 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Yin et al reported that the CRISPR-Cas9 tool could inhibit multiple steps of HIV-1 infection, 58 and several research labs have made excellent efforts to improve the use of CRISPR-Cas9 for treating HIV infection. 59–61 Recently, CRISPR-Cas12 and CRISPR-Cas13 systems have been used to inhibit HIV infection. 62 , 63 …”
Section: Preclinical Testsmentioning
confidence: 99%
“…The lentivirus-expressed Staphylococcus aureus Cas9 (saCas9)/gRNAs composed of multiple gRNAs targeting the conserved region in LTR and viral domain of HIV-1 effectively removed the latent HIV-1 virus, inhibited virus reactivation, and significantly improved the efficiency of destroying the HIV-1 genome [ 35 ]. More recent work and findings on gene therapy and editing of HIV-1 have been thoroughly reviewed and reported elsewhere [ 36 , 37 , 38 , 39 , 40 ]. In conclusion, these studies have demonstrated that the CRISPR/Cas9 system can be successfully applied to target and edit the HIV-1 genome, to inhibit HIV-1 infection, eliminate the virus, and even to induce the transcriptional activation of the latent virus to eliminate the virus, showing its potential use for HIV-1 therapy.…”
Section: Crispr/cas System In Virology Researchmentioning
confidence: 99%